Challenging cases in rheumatic disease pregnancy: management perspectives from reproductive rheumatologists - Mani, Iswariya; Bermas, Bonnie; Edens, Cuoghi; Sammaritano, Lisa; Zell, JoAnn; Birru Talabi, Mehret (Frontiers in Lupus, 2024)
Pregnant women with rheumatic and musculoskeletal diseases (RMDs) have a higher risk of adverse pregnancy and perinatal outcomes compared to those without RMDs. Although evidence-based guidelines have been developed for the reproductive health care and management of these individuals, multiple areas of uncertainty exist around the diagnosis and treatment of pregnant patients with confirmed or suspected RMDs. We present a series of outpatient cases that address areas of uncertainty in the field of reproductive rheumatology. Expert opinions were elicited from rheumatologists who have expertise in the reproductive health of individuals with RMDs to build new understanding around diagnosis or treatment approaches. The cases focused on the interpretation of antiphospholipid antibodies in various clinical scenarios, diagnosis and management of nephrotic-range proteinuria during pregnancy, and the use of tumor necrosis factor inhibitors during pregnancy. Our objective was not to replace existing guidelines and classification criteria but rather to provide a range of expert opinions that rheumatologists might consider when tailoring treatment and care for patients, particularly in challenging situations with limited data.